Impact of red cell distribution width on future risk of cancer and all-cause mortality among cancer patients – the Tromsø Study - Ellingsen, Trygve; Lappegård, Jostein; Skjelbakken, Tove; Brækkan, Sigrid Kufaas; Hansen, John-Bjarne (Haematologica, 2015)
Obtained from the Haematologica Journal website http://www.haematologica.org, available at http://dx.doi.org/10.3324/haematol.2015.129601